Rehabilitation of cardiological patients with post-COVID syndrome: morphofunctional data report - Guzal N. Sobirova; Stefano Masiero; Adibakhon A. Usmankhodjayeva; Makhfuza R. Bekchanova; Nikita A. Demin (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2024)
INTRODUCTION. Post-COVID is a common complication of COVID-19, occurring in more than a third of patients, and condition will persist for more than 3 months after infection with the SARS-CoV-2. AIM. To evaluate impact and potential effectiveness of a comprehensive physical rehabilitation program on health of cardiac patients with complications of a previously suffered new coronavirus infection SARS-CoV-2 COVID-19. MATERIALS AND METHODS. The study involved 128 cardiology patients with post-COVID syndrome. The study participants comprised three groups depending on the 12-week physical rehabilitation program. The effectiveness of rehabilitation was assessed through parameters of cardiopulmonary testing, as well as the 6-minute walk exercise test and the degree of dyspnea according to modified mMRC dyspnea questionnaire. RESULTS. The mMCR index in CPR group was 1.0 [0.0-1.0] point, compared with 2.0 [1.0-2.0] in control and comparative groups (p 0.05); exercise tolerance VO2max increased by 8.3 ± 3.8 % (p 0.05); normalization of heart rate and blood pressure in response to physical activity after 12 weeks in intervention group was 5.0 ± 2.1 % compared to comparative and control groups; 6MWT test results 688 m, in the intervention group, versus 490 m, for participants in control group (p 0.05). DISCUSSION. A comparative analysis of previously conducted studies confirmed pattern between the inclusion of combined cardiorespiratory training in the protocol for 12-week rehabilitation of post-COVID complications among cardiac patients, and a decrease in the degree of shortness of breath, as well as an increase in exercise tolerance. CONCLUSIONS. Based on experimental data obtained, it is advisable to analyze the effects of Cardiopulmonary Physical Rehabilitation program in the framework of larger randomized clinical trials. This will allow a more detailed assessment of the clinical consequences, as well as the ability to adjust mode and dose of physical activity of proposed rehabilitation program.